Influence of social cleavage and media usage on political behavior: a case of Pakistan - Anum, Isma; Zulfiqar, Amna (Frontiers in Political Science, 2024)
Increasingly media provides ample opportunities for the audiences to make media choices and form different levels of exposure along political lines. Predominately, Pakistan’s media is recognized as an irreplaceable tool in sparking change in the political landscape, forgoing national-regional identities, and bridging social gaps. Due to recent technological advancements citizens’ media usage brought changes in the political behavior of citizens regarding party choices and voting behavior. Such changes in the political behavior of citizens affect decision making which is influenced by social cleavage of education, gender, and age. However, contrary to similar historical changes, these advances have widened rather than narrowed societal cleavages. The objective of the paper is to explore the influence of social cleavage and media usage on political behavior of students and faculty in Pakistan specifically NUML university, Islamabad. This research explores how social cleavage and recent advances in digital media access changed the political behavior of faculty and students of NUML university. The paper employed survey-based research with a sample of 250 faculty members and students of NUML, Islamabad. According to results, it is concluded that social cleavage of education, age, and gender plays a vital role in transforming the political behavior of both faculty members and students. Likewise, persistent use of social media portrays positive political participation along with accountable voting behavior, whereby males are more active in participating in political activities as compared to females. The paper has policy implications for a one-dimensional media approach for ignoring solutions to political problems and understanding citizenship rights. Focused and well-defined policies are required to bring youth back to broadcasting media.